Profiling the segments of visitors in adventure tourism: comparison between visitors by recreational sites - Matthew, Nitanan Koshy; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman; Kunjuraman, Velan (Universiti Malaysia Sarawak, 2019)
The identification and understanding of the need of the customers are important for market segmentation specifically for tourism marketers. Failure to do such would fail to address the need of adventure visitors, and consequently resulting in dissatisfaction. Hence, this study focuses on the distinction between the sociodemographic, visit characteristics and customers’ satisfaction on recreation and facilities of adventure visitors at the recreational sites in Endau Rompin National Park (ERNP) namely the Endau Rompin Peta and Endau Rompin Selai. On-site data were collected from a sample of the visitors from both sites. The satisfaction of the visitors was evaluated using the perception analysis. In addition, cluster analysis was carried out. The study found that majority of the age of tourists is less than or equal to 30 years old, attained tertiary education level, earn above RM 5,000, single, visit in groups, first time visitors, knew the park through word of mouth, visit for leisure and recreation as well as team building, spent more than two days, stayed in camp and belong to the southern region in both recreational sites. The outcome is expected to be a guide for the operators of adventure tourism. This is aimed to facilitate plans toward formulating robust marketing strategies that would enhance the satisfactions of the visitors.